RETRACTED : Pengembangan instrumen asesmen literasi kimia pilihan ganda materi asam basa - Eli Khusmawardani; Muntholib Muntholib; Yudhi Utomo (Jurnal MIPA dan Pembelajarannya (JMIPAP), 2021)
Following a rigorous, carefully concerns and considered review of the article published in Jurnal MIPA dan Pembelajarannya (Journal of Mathematics, Science, and Instruction) to article entitle "Pengembangan instrumen asesmen literasi kimia pilihan ganda materi asam basa" Vol. 1 No. 6 (2021)This paper has been found to be in violation of the Jurnal MIPA dan Pembelajarannya (Journal of Mathematics, Science, and Instruction) publication principles and has been retracted.The article contained redundant material, the editor investigated and found that the paper published in AIP Conference ProceedingsThe document and its content has been removed from Jurnal MIPA dan Pembelajarannya (Journal of Mathematics, Science, and Instruction) and reasnable effort should be made to remove all references to this article.